2017
DOI: 10.1002/hbm.23545
|View full text |Cite
|
Sign up to set email alerts
|

Development of cortical motor circuits between childhood and adulthood: A navigated TMS‐HdEEG study

Abstract: Motor functions improve during childhood and adolescence, but little is still known about the development of cortical motor circuits during early life. To elucidate the neurophysiological hallmarks of motor cortex development, we investigated the differences in motor cortical excitability and connectivity between healthy children, adolescents, and adults by means of navigated suprathreshold motor cortex transcranial magnetic stimulation (TMS) combined with high-density electroencephalography (EEG). We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 115 publications
10
37
1
Order By: Relevance
“…In this study, TMS elicited a larger GMFP response in children compared to adults, with the responses in adolescents lying between those of children and adults. This finding is consistent with the results of our previous study using suprathreshold TMS of the motor cortex (Määttä et al, ), as well as with the results of other developmental TMS–EEG (Bender et al, ; Jarczok et al, ) and EEG studies (Matousek & Petersen, ; Tarokh & Carskadon, ; Whitford et al, ) demonstrating higher TEP amplitudes and EEG power in children and adolescents than in adults. With development, EEG shows a similar curvilinear decline to gray matter volume, and it has therefore been suggested that the smaller EEG responses in adults may be associated with gray matter loss in the prepubescent and peripubescent period (Whitford et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, TMS elicited a larger GMFP response in children compared to adults, with the responses in adolescents lying between those of children and adults. This finding is consistent with the results of our previous study using suprathreshold TMS of the motor cortex (Määttä et al, ), as well as with the results of other developmental TMS–EEG (Bender et al, ; Jarczok et al, ) and EEG studies (Matousek & Petersen, ; Tarokh & Carskadon, ; Whitford et al, ) demonstrating higher TEP amplitudes and EEG power in children and adolescents than in adults. With development, EEG shows a similar curvilinear decline to gray matter volume, and it has therefore been suggested that the smaller EEG responses in adults may be associated with gray matter loss in the prepubescent and peripubescent period (Whitford et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Following these lines of interpretation, the increased P180 in children in response to frontal cortex stimulation may reflect developmental differences in GABA B ergic neurotransmission and/or in frontal cortico–subcortical–cortical loops (e.g., through the thalamus [McFarland & Haber, ]). It is well‐known that the functional maturation of the GABAergic system continues until the end of adolescence (Kilb, ), and the GABA B hypothesis for the increased P180 in children is in line with the results from previous motor cortex TMS studies suggesting stronger inhibition in children compared to adults (Bender et al, ; Määttä et al, ; Säisänen et al, ). The functional significance of the suggested increase in inhibition in children remains uncertain.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations